Opportunities for Improving Environmental Compliance in Mexico - Dasgupta, Susmita 1961- (The World Bank, 1999)
One of the main reasons for noncompliant firms' poor environmental performance is the information gap on Mexico's environmental policy. Pollution control could be improved through systematically fuller communication targeted to noncompliant firms - including more environmental education, especially of senior managers. - Survey evidence from Mexico reveals large observed differences in pollution from factories in the same industry, or the same area, or operating under the same regulatory regime. Many factories have adopted significant measures for pollution control and are in compliance with environmental regulations, but some have made little or no such effort. For lack of data, systematic research on the reasons behind such variations in plant-level environmental performance (especially on how impediments to pollution control affect plant behavior) is rare, even in industrial societies. Drawing on a recent plant-level survey of Mexican factories, Dasgupta identifies a number of performance variables characteristic of compliant and noncompliant plants, as well as factors that non-compliant plants perceive to be obstacles to pollution control. Noncompliant firms made less effort than compliant firms to change materials used, to change production processes, or to install end-of-pipe treatment equipment. They had significantly fewer programs to train their general workers in environmental responsibilities. They lagged behind in environmental training, waste management, and transportation training. They received less technical training, especially about the environment, environmental policy and administration, and clean technology and audits. Responses about obstacles to better environmental performance included scarcity of training resources, government bureaucracy, high interest rates, and Mexico's lack of an environmental protection culture.